PERFORMANS REPRODUKSI SAPI PESISIR DAN SAPI BALI . DI DAERAH INSEMINASI BUATAN KECAMATAN BAYANG KABUPATEN PESISIR SELATAN - Yendraliza Yendraliza (Jurnal Peternakan, 2005)
Th~ research rums to kn~~ the comparison of Pesisir and Bali c~ws reproductive perfvrmances in artificial~nsem~natlon ar~a! Bayang~ Peslslr Selatan. Data was collected using sample accidental methode on 130 and 41msemmated Peslslr and Ball cows respectively. The data was analyzed using t and z tests. .. The. result ~ho.wed that the first se,rvice after calving rate and the calving interval ofPesisir and Bali cows weredl~e~ent highly. slgruficant but the calvmg rate are different significantly. The first service after calving rate ofPeslslr .and Balt cows are 268.7~ and 211.86 days, and the calving interval of the are 545.12 and 500.63 days. respectively. Furthermore the calvmg rate ofthem are 73.07% and 50% and the pregnant periode are 277.39 and 278 days respectively.